Model 3D Mineral Hematite Berdasarkan Data Geomagnet di Desa Uekuli Kabupaten Tojo Una-Una (3D Model of Hematite Mineral Based On Geomagnetic Data in The Uekuli Village Tojo Una-Una Regency) - Parhusip, Jaingot A.; Rusli M, Muhammad (PROMINE, 2015)
Uekuli Village Tojo Una-Una Regency, have potential of natural resources such as iron sand that containing mineral hematite which is a basic ingredient on the steel industry. This is evidenced by the deposition of iron sand and iron ore rock outcrops in the area. To determine the magnitude of the potential distribution of the iron ore it has performed geophysical exploration using geomagnetic methods. Research by using geomagnetic done through the stages; acquisition of field data, make corrections IGRF and daily variation correction, modeling using 3D modeling software Mag2dc and with help of rockwork software. Results of the study, found that the magnetic anomaly data has avalue range between -120 nT to +160 nT. Magnetic minerals contained in the iron ore is hematite. Estimation volume of distribution of mineral hematite are 377 300 m3.Keywords: Geomagnetic, IGRF, Mag2dc, 3D Models, Hematite.